2008
DOI: 10.1002/chem.200801676
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Metal‐Free Enantioselective Conjugate Addition Reactions of Zinc Reagents

Abstract: Asymmetric conjugate addition of diethylzinc to cinnamaldehyde in a co-metal-free fashion by using N,O-ligands with planar and central chirality is described. Different modulations of the ligand structure, including several combinations of the chiral units, indicate that a [2.2]paracyclophane backbone is essential for the activity and the enantioselectivity of the generated active catalyst. By using the optimized ligand, an isolated yield of 90 % was obtained with up to 99 % ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 115 publications
0
26
0
Order By: Relevance
“…Further investigations, for example, by Noyori and Soai,9,10 showed that catalysis with [2.2]paracyclophane zinc complexes having a nitrogen–oxygen coordination motif is feasible. In recent years, we combined the rigidity of the [2.2]paracyclophane backbone with novel metal coordinating moieties and described the asymmetric conjugate addition (ACA) of diethylzinc to cinnamaldehyde utilizing different [2.2]paracyclophane ligands 1113. In this publication we present a series of new [2.2]paracyclophane derivatives bearing N‐heterocycles with various substitution patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations, for example, by Noyori and Soai,9,10 showed that catalysis with [2.2]paracyclophane zinc complexes having a nitrogen–oxygen coordination motif is feasible. In recent years, we combined the rigidity of the [2.2]paracyclophane backbone with novel metal coordinating moieties and described the asymmetric conjugate addition (ACA) of diethylzinc to cinnamaldehyde utilizing different [2.2]paracyclophane ligands 1113. In this publication we present a series of new [2.2]paracyclophane derivatives bearing N‐heterocycles with various substitution patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the enantioselective copper‐catalyzed conjugate addition of organometallic reagents using different types of chiral ligand systems on the metal provides high stereocontrol 3. This research has shown that the direct transition‐metal‐catalyzed enantioselective 1,4‐addition of an organometallic reagent to an α,β‐unsaturated aldehyde 5 in the presence of a chiral ligand is very challenging due to a competing 1,2‐addition reaction, which gives both the β‐aldehyde 6 and alcohol 7 , respectively (Scheme ) 4bc. 5…”
Section: Methodsmentioning
confidence: 99%
“…Aminoalcohols can be used as convenient catalysts for 1,2‐additions 1. To obtain a 1,4‐product, one should either use special Hoveyda‐type catalysts with the addition of a copper salt2 or [2.2]paracyclophane‐based N,O‐ligands 3. The second route has the key advantage that it does not involve any co‐metals and therefore is more convenient.…”
Section: Introductionmentioning
confidence: 99%
“…Bräse et al. examined a series of paracyclophane‐containing catalysts and proved its utility, especially for addition reactions to enals3 and iminals4 (Scheme ). However, in the case of iminals, the 1,4‐addition product was clearly favoured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation